2022
DOI: 10.3390/app12094384
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of DRNN for Identifying Built Environment Barriers to Walkability Using Wearable Sensor Data from Pedestrians’ Gait

Abstract: Identifying built environment barriers to walkability is the first step toward monitoring and improving our walking environment. Although conventional approaches (i.e., surveys by experts or pedestrians, walking interviews, etc.) to identify built environment barriers have contributed to improving the walking environment, these approaches may require time and effort. To address the limitations of conventional approaches, wearable sensing technologies and data analysis techniques have recently been adopted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…Limited studies have applied deep neural networks to analyze human responses for walking surface condition detection. Kim et al verified the effectiveness of a cascaded LSTM-based deep recurrent neural network method to classify abnormal and normal gaits, and demonstrated that the ratio of abnormal gaits could indicate the existence of an environmental barrier to walkability, as they were highly correlated [37]. The confirmed relationship between the ratio of abnormal gaits and the presence of an environmental barrier is in line with our observation of a higher rate of disrupted gaits on irregular walking surface segments.…”
Section: Deep Learning Methods For Automated Sidewalk Assessmentssupporting
confidence: 83%
“…Limited studies have applied deep neural networks to analyze human responses for walking surface condition detection. Kim et al verified the effectiveness of a cascaded LSTM-based deep recurrent neural network method to classify abnormal and normal gaits, and demonstrated that the ratio of abnormal gaits could indicate the existence of an environmental barrier to walkability, as they were highly correlated [37]. The confirmed relationship between the ratio of abnormal gaits and the presence of an environmental barrier is in line with our observation of a higher rate of disrupted gaits on irregular walking surface segments.…”
Section: Deep Learning Methods For Automated Sidewalk Assessmentssupporting
confidence: 83%